Usos das águas da sub-bacia hidrográfica do rio Pagão em Umbaúba-SE - Nascimento, Raimunda Joysse Pereira dos Reis (2022)
Questions about the availability of water on the earth's surface are increasingly current. Since the emergence of life on Earth, water has been a primordial element for the maintenance of life. The technological advance acquired by man, more markedly in the post-Industrial Revolution, has increasingly enabled the exploitation of nature and its resources, including water. This expressive consumption has directed the eyes of the world to discussions about the preservation and maintenance of such a scarce resource. The objective of this work is to identify the uses attributed to the waters of the Pagão River sub-basin in Umbaúba-SE. For this work, we adopted the categories Territory, Landscape and the Hydrographic Basin cutout, considering that the uses of water delimit territories and modify the landscapes. To obtain the results, the methodology used went through stages of bibliographic and documental research, field work and analysis and construction of cartographic material. The results achieved show that the uses of water in the sub-basin comply with the national use pattern, with the abstraction being mostly focused on agricultural uses, urban human supply, rural human supply, industrial in addition to non-consumptive uses such as fishing and leisure. The studies carried out also indicate that the uses applied to the waters of the subbasin condition conflicts of interest. In this way, we hope, with this work, to raise discussions related to water management and maintenance of the drainage network in the municipality of Umbaúba and in the sub-basin as a whole.